Oleuropein Detemination In Dried Olive Leave Water Extract By DPV Using Lead Electrically Modified Pencil Electrode (Damascus University Journal for the basic sciences, 2022)
Lead pencil electrode was modified by scanning voltammetry in a  mixture of nitric acid and lithium perchlorate electrolyte. The electrode was used as a sensor to determine oleuropein in extract of dried olive leaves extract. oleuropein is the highest available component among of the polyphenols in the olive leave extract. ( DPV) differential striping voltammetry technique was utilized with EIS to characterize the modified electrode. A noticeable enhancement of electrode. Electrochemical reactivity was noticed an oxidation maximum appeared at 0.5V as a result of Ole oxidation with linear change of its current light versus Ole concentration.(range: 5.4*10-4M  ̶  8.8*10-5 M) with Dl=5.4*10-5M at accumulation time =2 min and the value of the R2=0.989  the described electrode has a lower residual current, no was than 10µA. All effective parameters was studied (e.g: v, PH, t)
Keywords: Pencil Electrode; Oleuropein; Cyclic Voltammetry Cv; Technique Differential Pulse Anodic Stripping Voltammetry (Dpas